Current Trends and Emerging Paradigms in the Treatment of Alopecia Areata - Feretycki, Hubert; Kaminskaya, Anhelina; Kurek, Aleksandra; Salama, Aladdin; Głowacka, Aleksandra; Savchak, Tetiana; Górecki, Patryk; Ivanchuk , Sofiia; Domińczak, Dominika; Abdulla, Shafea (Quality in Sport, 2026)
Background: Alopecia areata (AA) is an unpredictable, immune-mediated form of non-cicatricial hair loss driven by the collapse of hair follicle immune privilege. Beyond its physical manifestation, the highly visible nature of AA inflicts a profound psychosocial and emotional burden on adult, adolescent, and pediatric populations, severely degrading their quality of life. Aim: This review evaluates the current trends and major paradigm shifts in the therapeutic landscape of AA, analyzing the transition from traditional, non-specific immunosuppression to targeted molecular and regenerative interventions based on high-level evidence up to 2026. Materials and methods: A comprehensive synthesis of peer-reviewed literature - including systematic reviews, network meta-analyses, and recent Phase III clinical trial data - was conducted to evaluate the comparative efficacy, safety profiles, and clinical positioning of established and emerging therapies. Results: Janus kinase inhibitors (baricitinib, ritlecitinib, and deuruxolitinib) demonstrate superior efficacy in moderate-to-severe AA, achieving significant scalp hair regrowth (SALT score of 20 or less). Concurrently, regenerative therapies like exosomes and platelet-rich plasma (PRP) offer effective local alternatives, while structured psychological support significantly reduces patient anxiety and depression. Conclusion: Targeted and regenerative modalities have fundamentally redefined AA care. However, long-term success is challenged by high relapse rates post-discontinuation and socioeconomic barriers, highlighting the need for personalized maintenance protocols.